Love, Stargirl - Spinelli, Jerry (Knopf, 2007)
Still moping months after being dumped by her Arizona boyfriend Leo, fifteen-year-old Stargirl, a home-schooled free spirit, writes "the world's longest letter" to Leo, describing her new life in Pennsylvania.